EFEKTIFITAS PEMBELAJARAN DARING MATA PELAJARAN FIKIH (TEMA HAJI DAN UMROH) PADA PENINGKATAN MOTIVASI DAN HASIL BELAJAR SISWA MASA PANDEMI COVID – 19 DI SERANG BANTEN - Enung nuraeni; Muhajir Muhajir (Program Studi Pendidikan Agama Islam Program Pascasarjana Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2022)
This study aims to determine the effectiveness of online learning for fiqh subjects (hajj and umrah themes) in increasing student motivation and learning outcomes during the COVID-19 pandemic at MTs. Al-Hidayah Attacks Banten. The occurrence of the COVID-19 pandemic in Indonesia has an impact on the world of education. One of the ways to prevent its spread is that people are prohibited from gathering together, staying at home, this has an impact on students in teaching and learning activities, effective learning activities are needed in this pandemic situation. To get maximum learning outcomes as expected, an effective learning method is needed according to the conditions of students. In this case, an effective teaching and learning activity during the COVID-19 pandemic is online learning. The method used is Descriptive Quantitative Research Method, while the results of this study indicate: The effectiveness of the Online Learning Model for Jurisprudence subjects to increase students' motivation and learning outcomes during the COVID-19 pandemic at MTs Al-Hidayah Ciomas is very effective which has the contribution of variable X to variables Y1 is 72, 9% and variable X to variable Y2 is 82.8%,